2020
DOI: 10.3390/medicines7040019
|View full text |Cite
|
Sign up to set email alerts
|

Piperine Inhibits TGF-β Signaling Pathways and Disrupts EMT-Related Events in Human Lung Adenocarcinoma Cells

Abstract: Background: Piperine, an amide extracted from the Piper spices, exhibits strong anti-tumor properties. However, its effect on the epithelial–mesenchymal transition (EMT) process has never been investigated. Herein, we evaluate the toxic effect of piperine on lung adenocarcinoma (A549), breast adenocarcinoma (MDA-MB-231) and hepatocellular carcinoma (HepG2) cell lines, as well as its ability to inhibit EMT-related events induced by TGF-β1 treatment. Methods: The cell viability was investigated by MTT assay. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 90 publications
(123 reference statements)
2
16
0
Order By: Relevance
“…Data analysis was performed with the LineGene 9600 plus Real-Time PCR for Research software. 33 All procedures were performed according to the manufacturer’s instructions. The PCR reactions were performed using the primers described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Data analysis was performed with the LineGene 9600 plus Real-Time PCR for Research software. 33 All procedures were performed according to the manufacturer’s instructions. The PCR reactions were performed using the primers described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the A549/KL-1 cell line with stable Klotho overexpression was established. It was reported that Klotho inhibited TGF-β1-induced EMT responses ( 45 , 46 ). Also, it was demonstrated that Klotho is capable of inhibiting the activation of the Wnt signaling pathway, which inhibits glycogen synthase kinase-3β ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different molecular pathways act as upstream mediators of EMT in cancer progression. TGF-β signaling pathway is an EMT inducer in cancer cells and in this way, can provide chemoresistance [ 123 , 124 ]. PI3K/Akt signaling can also induce EMT in cancer cells, and its downregulation is associated with a decrease in EMT [ 125 , 126 ].…”
Section: Curcumin In Combination With Doxorubicinmentioning
confidence: 99%